Comparison of biological responses between submerged, pseudo-air-liquid interface, and air-liquid interface exposure of A549 and differentiated THP-1 co-cultures to combustion-derived particles. Issue 7 (22nd July 2022) - Kaur, Kamaljeet; Mohammadpour, Raziye; Sturrock, Anne; Ghandehari, Hamidreza; Reilly, Christopher; Paine, Robert; Kelly, Kerry E.
Abstract: Air liquid interface (ALI) exposure systems are gaining interest, and studies suggest enhanced response of lung cells exposed to particles at ALI as compared to submerged exposure, although the results have been somewhat inconsistent. Previous studies have used monocultures and measured particle deposition using assumptions including consistent particle deposition, particle density, and shape. This study exposed co-cultures of A549 and differentiated THP-1 cells to flame-generated particles using three exposure methods: ALI, pseudo-ALI, and submerged. The dose at ALI was measured directly, reducing the need for assumptions about particle properties and deposition. For all exposure methods an enhanced pro-inflammatory response (TNFα) and Cytochrome P450 (CYP1A1) gene expression, compared to their corresponding negative controls, was observed. ALI exposure induced a significantly greater TNFα response compared to submerged exposure. The submerged exposures exhibited greater induction of CYP1A1 than other exposure methods, although not statistically significant. Some of the factors behind the observed difference in responses for the three exposure methods include differences in physicochemical properties of particles in suspending media, delivered dose, and potential contribution of gas-phase species to cellular response in ALI exposure. However, given the difficulty and expense of ALI exposures, submerged exposure may still provide relevant information for particulate exposures.